Arsenic and other heavy metals in the Sunkoshi and Saptakoshi Rivers, eastern Nepal - Emerman, Steven H.; Anderson, Ryan B.; Bhandari, Sushmita; Bhattarai, Roshan R.; Palmer, Mallory A.; Bhattarai, Tara N.; Bunds, Michael P. (Journal of Nepal Geological Society, 2011)
Available with full text.